2017
DOI: 10.1534/genetics.116.195776
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Behavioral Effects of MicroRNA Regulation inDrosophila

Abstract: Picao-Osorio et al. reveal pervasive effects of microRNA regulation on complex locomotor behaviors in Drosophila larvae: over 40% of microRNAs display...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 69 publications
0
33
0
1
Order By: Relevance
“…Similar to other model organisms 14 , only few fly miRNA deletions exert lethal phenotypes or strong morphological abnormalities. However, many miRNA have been found have subtle effects 15,16 , which become more pronounced when the organism is challenged. It remains difficult to describe direct organismic miRNA effects via individual targets in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other model organisms 14 , only few fly miRNA deletions exert lethal phenotypes or strong morphological abnormalities. However, many miRNA have been found have subtle effects 15,16 , which become more pronounced when the organism is challenged. It remains difficult to describe direct organismic miRNA effects via individual targets in a quantitative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our screens of adult locomotion, a large fraction (44 of 128; 34%) of our miR-SP lines induced a significant effect on one or more locomotor parameters in L2 stage larva ( Figure 5). This percentage of hits was approximately equal to the frequency of miRNA hits in an early larval deficiency screen selective to self-righting behavior (Picao-Osorio et al 2017), confirming that many miRNAs play some role in establishing normal motor circuitry, but that many of the effects may not be selective to particular motor responses. Despite the large number of hits, we found larval phenotypes to exhibit a greater degree parameter selectivity than the neurally-driven miR-SPs assayed in early adulthood.…”
Section: Mirna Regulation Of Larval Locomotionmentioning
confidence: 74%
“…These studies argue that miRNAs provide a potentially important level of regulation in motor circuits, but the use of null mutants and chronic global manipulations did not allow investigators to disambiguate developmental and functional roles or to understand the tissue-specificity of miRNA actions. Recently, using a very specific assay for early larval self-righting behavior to screen many deletion alleles, a surprisingly large number miRNA were shown to modulate various aspects of this simple patterned motor response (Picao-Osorio et al 2017). Interestingly, multiple miRNA hits in this focused screen appear to converge on the developmental patterning gene Abdominal-B (Abd-B), a HOX-class transcription factor (Picao-Osorio et al 2017), suggesting that developmental events are a major target of translational regulation.…”
Section: Microrna Motor Behavior Drosophila Melanogastermentioning
confidence: 99%
“…Larval SR behaviour was assayed as previously described (Picao-Osorio et al, 2015;Picao-Osorio et al, 2017) . For adult SR behaviour tests, flies were grown in non-crowed conditions at 25ºC.…”
Section: Self-righting Testsmentioning
confidence: 99%
“…Our previous work showed that miR-iab4 affects larval movement through regulation of one of its molecular targets, the Hox gene Ultrabithorax (Ubx), whose level of expression in a set of metameric motor neurons is critical for normal SR behaviour (Picao-Osorio et al, 2015). To explore the generality of the effects of miRNA regulation on larval SR movement we recently conducted a genetic screen that revealed that at least 40% of all miRNAs expressed in young Drosophila larva can affect SR demonstrating an unprecedented and widespread role of miRNA regulation in the control of postural adjustments and locomotor behaviour (Picao-Osorio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%